Understanding challenges and opportunity of data recording and reporting of malnutrition intervention programs: A qualitative study among healthcare workers in DKI Jakarta - Aryanti Mayadewi, Chyntia; Novita Chandra, Dian; Februhartanty, Judhiastuty (Indonesian Nutrition Association, 2025)
Background: The number of stunting in Indonesia was reported to be 21.6% in 2022, still far from the 2024 target of 14%. The large-scale programs of nutrition-specific intervention have been done, including moderate-acute malnutrition (MAM) and severe-acute malnutrition (SAM) interventions. However, limited findings on the process of monitoring and evaluation of both interventions. Objective: This paper aims to describe the implementation, challenges, and opportunities of malnutrition intervention data recording and reporting among healthcare workers in DKI Jakarta Province, Indonesia. Methods: Qualitative data collection was taken with in-depth interview (IDI) and focus group discussion (FGD) in August-October 2024 towards healthcare workers in selected Puskesmas in DKI Jakarta who were involved with MAM and SAM interventionss and data management. Data triangulation was done to health cadres and mothers of children under five (CU-5) as the beneficiaries. Results: This study involved eight informants from South and Central Jakarta Puskesmas, and 16 cadres and 13 mothers who were involved in MAM and SAM interventionss. The dissemination and adaptation of indicators has been done and digital data recording has been used, despite its lack of supporting resources and data integration which may affect its data quality. Leveraging resources and enabling data-sharing between facilities and maintaining communication between stakeholders are essential. Conclusions: The process of data recording and reporting of malnutrition interventions required well-informed indicators, trained personnel, and streamlined information systems. Maintaininghigh quality data, collaboration between stakeholders and utilizing accessible technology are recommended for the healthcare worker to improve the process of data recording and reporting.